THE ROLE OF COLLABORATIVE LEARNING IN ENHANCING STUDENTS’ SPEAKING ABILITIES - Qudratillah, Navilatur Rahmi; Ferdiyanto, Feri; Islam, Raudhatul (International Journal of Research on English Teaching and Applied Linguistics, 2025)
This study aimed to determine the role and effectiveness of collaborative learning in enhancing the English speaking abilities of class X students at MAN 1 Situbondo. The research method used was descriptive qualitative, with data collection techniques in the form of observation, interviews with English teachers, and the distribution of questionnaires to students. The results of the study indicated that collaborative learning enhanced students' speaking fluency, vocabulary mastery, and self-confidence. Group discussions applied in learning created an environment that supported and encouraged students to be more active in participating in speaking English. Most students responded positively to this method, with the majority feeling more motivated, practicing speaking more often, and experiencing enhancements in pronunciation. Thus, collaborative learning proved effective as a strategy to enhance students' English speaking abilities while preparing them to face the challenges of communication in the global era.